INKLUSI SOSIAL DALAM PERSPEKTIF KEISLAMAN: MENINGKATKAN KESEJAHTERAAN SOSIAL UNTUK SEMUA - Sitti Faoziyah (AKSELERASI: Jurnal Ilmiah Nasional, 2023)
In an Islamic perspective, social inclusion has a broad and deep meaning. Concepts such as ukhuwah islamiyah, musawah, and ihsan can become the basis for encouraging broader and more sustainable social inclusion in society. This study aims to identify and analyze Islamic concepts related to social inclusion, as well as to explore how an Islamic perspective can help improve social welfare for all levels of society. A qualitative approach was used in this study with descriptive data analysis. The results of the research show that Islamic concepts such as ukhuwah islamiyah, musawah, and ihsan can be the basis for encouraging broader social inclusion in society. These concepts emphasize the importance of solidarity, equality and justice in interacting with fellow individuals and society. In addition, the Islamic perspective also teaches values such as tolerance, diversity, and empathy which can help improve social welfare for all levels of society.